2009
DOI: 10.1109/tit.2009.2025528
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Robust Compressed Sensing Using Optimized Expander Graphs

Abstract: Abstract-Expander graphs have been recently proposed to construct efficient compressed sensing algorithms. In particular, it has been shown that any n-dimensional vector that is k-sparse can be fully recovered using O(k log n) measurements and only O(k log n) simple recovery iterations. In this paper, we improve upon this result by considering expander graphs with expansion coefficient beyond 3 4 and show that, with the same number of measurements, only O(k) recovery iterations are required, which is a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
209
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(211 citation statements)
references
References 22 publications
2
209
0
Order By: Relevance
“…Since the increase in the number of paths, which corresponds to the number of measurements, results in the increase in the number of probe packets injected into the network, it is desirable to minimize the number of paths in order not to give unnecessary load to the network. As for the number of required measurements for the reconstruction of k-sparse vectors with random binary measurements matrices, it has been known that O(k log n k ) measurements are required [153], [154], while it has been shown that O(k log n) measurements are needed if the binary matrix is accompanied by a graph constraint [151], [155]. Moreover, a deterministic guarantee and a designed method of the routing matrix for the reconstruction of any 1-sparse signal are provided in [149], [150], taking advantage of the knowledge on compressed sensing using expander graphs [154], [156].…”
Section: Network Tomographymentioning
confidence: 99%
“…Since the increase in the number of paths, which corresponds to the number of measurements, results in the increase in the number of probe packets injected into the network, it is desirable to minimize the number of paths in order not to give unnecessary load to the network. As for the number of required measurements for the reconstruction of k-sparse vectors with random binary measurements matrices, it has been known that O(k log n k ) measurements are required [153], [154], while it has been shown that O(k log n) measurements are needed if the binary matrix is accompanied by a graph constraint [151], [155]. Moreover, a deterministic guarantee and a designed method of the routing matrix for the reconstruction of any 1-sparse signal are provided in [149], [150], taking advantage of the knowledge on compressed sensing using expander graphs [154], [156].…”
Section: Network Tomographymentioning
confidence: 99%
“…The performance of convex optimizations for sparse estimation in this setting were examined in [34]. Greedy and other ad-hoc procedures for signal estimation in such settings were examined in [35]- [38].…”
Section: Connections With Existing Workmentioning
confidence: 99%
“…There are two different recovery approaches for e-CS in the literature: Combinatorial approach [4], [5]: In this approach, messagepassing algorithms are proposed for approximating x * . The recovery algorithms rely on the combinatorial properties of these graphs, and have lower computational complexity (e.g., O(N log N k )).…”
Section: Expander-based Compressed Sensingmentioning
confidence: 99%
“…Messagepassing algorithms [4], [5] exploit the combinatorial structure of the expander graphs. While these algorithms are efficient and rather easy to implement, their approximation guarantees are meaningful only in extremely high-dimensions, as they feature large constants that are not suitable for practical applications.…”
Section: Introductionmentioning
confidence: 99%